ANALYSIS OF CHANGES IN INTRAOCULAR PRESSURE WITH CHANGES IN BODY POSITION - Karim, Samina; Khan, Muhammad Naeem; Hussain, Zakir; Mohammad, Saber (Journal of Postgraduate Medical Institute, 2012)
Objective: To find out the patterns of changes in Intraocular Pressure (IOP) with changes in body position,both in the sitting and lying position. Methodology: This descriptive study was conducted at Hayatabad Medical Complex, Peshawar fromOctober 2010 to March 2011. All the individuals who voluntarily consented were included in the study.These include individuals without any eye pathologies, glaucomatous eyes, eyes with cataract and bothhospitalized and non-hospitalized individuals. While all the individuals who have any corneal pathologies,uveitis, detachment, post operative and post lasered eye were excluded from the study. All the patients wereexamined with slit lamp. Then Perkins' hand-held applanation tonometer was used to measure the IOPboth in the sitting and lying position. The proforma was then filled and data was analyzed by using SPSSv.17. Results: A total of 100 volunteers were included in our study while total number of eyes were two hundred.The mean age of the sample was 49±15.4 years. There were 110(55%) males and 90(45%) females.Hypertension was present in 50(25%) patients and all of them were taking antihypertensive medications.Thirty five (17.5%) were diabetic and were also on medications. The mean IOP in the sitting position was13.28±3.6 mmHg and in lying position it was 16.4±3.9 mmHg. The difference between lying and sittingposition was 3.12±0.3 mmHg (p<0.001). Conclusion: A postural IOP change can occur when an individual changes its position from sitting tosupine position. Intraocular pressure increases in the lying position as compared to the sitting position.